2017
DOI: 10.1038/s41598-017-16978-y
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Expression in Ethnic Specific Early Stage Breast Cancer: an Integration and Comparative Analysis

Abstract: Breast cancer (BC) has a higher incidence in young Lebanese woman as compared to the West. We assessed the microRNA (miRNA) microarray profile of tissues derived from Lebanese patients with early BC and performed mRNA-miRNA integration analysis. 173 miRNAs were significantly dysregulated in 45 BC versus 17 normal adjacent breast tissues, including 74 with a fold change more than two of which 17 were never reported before in cancer. Integration analysis of mRNA-miRNA microarray data revealed a potential role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…miR-183 upregulation coincides with the results of a study by Chen et al where miR-183, in addition to miR-21 and miR-200c were find to be significantly upregulated in the FFPE breast cancer tissues [25]. This was also noted in a study on Lebanese FFPE breast cancer tissues [20,31]. miR-182 upregulation was noted in more than one study where its fold change of expression is usually more than 4 folds higher in cancerous breast tissue than in paracancerous tissue [32].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…miR-183 upregulation coincides with the results of a study by Chen et al where miR-183, in addition to miR-21 and miR-200c were find to be significantly upregulated in the FFPE breast cancer tissues [25]. This was also noted in a study on Lebanese FFPE breast cancer tissues [20,31]. miR-182 upregulation was noted in more than one study where its fold change of expression is usually more than 4 folds higher in cancerous breast tissue than in paracancerous tissue [32].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it was difficult to obtain some of the clinical characteristics of some patients due to cross country and institutional barriers. miR-21, miR-183, miR-182, miR-425-5p and miR-200c were found to be upregulated in tumor versus normal adjacent breast tissues, similar to the Lebanese patients and patients in other studies reported in the literature [20,25]. This study is the first to report the patterns of miRNA dysregulation in the Algerian population, one of North African populations that are known to possess great gene pool heterogeneity from Eurasia, Sub Saharan Africa and North Africa [49].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Breast cancer has a higher incidence in young Lebanese women as compared with American woman. A comparative profiling study showed that, in Lebanese breast cancer patients, 21 miRNAs, including miR-663 , were specifically deregulated, possibly as a result of differential methylation of their promoter [ 46 ]. Another study showed that miR-663 is up-regulated in multidrug-resistant MDA-MB-231-derived ADM cell line, and that increased miR-663 expression was associated with the downregulation of Heparin sulfate proteoglycan 2 (HSPG2) and chemoresistance [ 47 ].…”
Section: Resveratrol-inducible Mir-663 In Healtmentioning
confidence: 99%